Evaluation of Posture and Quality of Life in Females Undergone Modified Radical Mastectomy: A Research Protocol - Aachal Birelliwar1 , Shalaka Dhankar2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Modified radical mastectomy performed for CA breast is a life modifying surgery for most women. It createsa profound impact on the quality of life enjoyed by the women. Body image in patients with breast cancerdiffers from all other cancers. The assessment of quality of life after modified radical mastectomy for earlybreast cancer patients using the World Health Organization Quality of Life-Brief Questionnaire (WHOQOLBREF) .Women suffers from day to day activities. Postures become impaired. Postural changes, such as increase inthoracic kyphosis , scoliosis leads to poor postural habits. There is also decrease in shoulder range of motion, scapular muscles weakness . Contractures may develop in axilla after surgery. Breast cancer survivors havemuscle weakness of upper limb are Pectoralis major, serratus anterior, upper trapezius, rhomboid muscles,latissimus dorsi .Spine alignment also may effect due to poor posture. Women with Modified Radical mastectomy may havesome social phobia . Anxiety, stress level may increase. Women may have fear of recurrence. Because of thisfactors , there is impaired Quality of Life in Women.Conclusion: Breast cancer is a serious disease that reduces the quality of life, particularly in physical domainand in the emotional area. Oncological disease is becoming a disease for a lifetime. It connected with theconstant fear of cancer recurrence and the consequences of treatment.